A 2100MPa high-strength multiphase hot-rolled wire rod for bridge cables and a manufacturing method thereof

By using C-Si-Mn-Cr-Mo chemical composition and online molten salt end quenching isothermal technology in hot-rolled strips for 2100MPa-grade bridge cables, the problem of difficult to control the abnormal structure of mesh carbides and martensite in the prior art is solved, and high-strength and low-cost hot-rolled strips are achieved, reducing the risk of wire breakage.

CN119265486BActive Publication Date: 2025-05-02JIANGSU YONGGANG GROUP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411815159.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-05-02
Estimated Expiration
2044-12-11

Smart Images

  • Figure CN119265486B_ABST
    Figure CN119265486B_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength multiphase hot-rolled wire rod for 2100MPa bridge cables and a manufacturing method thereof. After rolling and spinning into wire rods with a chemical composition of C‑Si‑Mn‑Cr‑Mo, the wire rods are subjected to an online molten salt terminal quenching isothermal treatment, so that the wire rods first pass through a front-stage molten salt and are cooled at a cooling rate of ≥35°C / s to enter a sorbite phase region from an austenite state, and part of the austenite is controlled to transform into the sorbite. The wire rods are then cooled to a bainite phase through a rear-stage molten salt for terminal quenching, and the bainite phase transformation and isothermal tempering are controlled to relieve stress. Finally, the wire rods are subjected to roller slow cooling to form a multiphase structure including tempered sorbite and tempered bainite. The wire rods can effectively control abnormal structures of network carbides and martensite, realize high-strength multiphase structure regulation and plastic matching, have a tensile strength of 1530-1560MPa, and a cross-sectional shrinkage of 30%-35%. The wire rods are suitable for manufacturing 2100MPa ultra-high-strength bridge cables with a large drawing volume, and are conducive to reducing the risk of wire breakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hot-rolled wire rods, and specifically relates to a high-strength multi-phase hot-rolled wire rod for 2100MPa-level bridge cables and a manufacturing method thereof. Background Art

[0002] High carbon pearlite steel has excellent drawing properties and is often used in the field of large drawing volume and high strength. As bridges gradually develop towards ultra-high strength, more stringent requirements are placed on the ultra-high strengthening of hot-rolled wire rod parent materials for 2100MPa-grade bridge cables. The carbon content and alloy content of high carbon pearlite steel continue to increase, but the greater the drawing volume, the higher the requirements for the uniformity of the wire rod's organization and the drawing processing performance. Under conventional controlled rolling and cooling production lines, the deteriorated organizations such as network carbon and martensite in the production process of hot-rolled wire rod parent materials are becoming increasingly difficult to control. In the subsequent large-scale drawing processing of bridge cable manufacturing, the risk of wire breakage is very likely to occur. Therefore, the development of a hot-rolled wire rod parent material suitable for stable large-scale drawing processing to manufacture 2100MPa-grade bridge cables is an issue that is currently urgently needed to be addressed.

[0003] The technical difficulties and causes that limit the performance and manufacturing of existing 2100MPa grade hot-rolled wire rods for bridge cables include:

[0004] 1. In order to achieve ultra-high strengthening of hot-rolled wire rods, most wire rods adopt a high-carbon and high-silicon component system, and add Nb, V, and Ti carbonitride-forming elements to refine the grains, and combine with the Stelmor air-cooled wire after spinning to form fine pearlite, that is, sorbite structure. However, on the one hand, the high carbon content aggravates the segregation tendency during the solidification of the steel billet. Limited by the maximum cooling capacity of the air-cooled wire, it is easier to precipitate a large amount of secondary cementite along the grain boundary and aggregate into a network carbide, destroying the continuity of the matrix, deteriorating the plasticity and toughness of the wire rod, and causing wire breakage during drawing. In order to minimize the influence of network carbides, the air-cooling intensity will be increased as much as possible before the phase change after spinning, or further combined with water mist or water bath cooling. For example: Patent CN116145036A discloses a hot-rolled wire rod and production method for galvanized steel wire for bridge cables of 2100MPa and above, which adopts a C-Si-Mn-Cr-Al-V-Nb-Ti component system, combined with online thermal relaxation and water bath cooling after spinning. It is a hot-rolled wire rod with a sorbite content of ≥95%. However, under strong wind cooling, the air volume and wind speed are more uncontrollable, which will further increase the temperature difference between the windward side and the leeward side of the wire rod, the temperature difference from the upper edge to the core of the same cross-section of the wire rod, and the temperature difference between the overlap and the non-overlap. Water cooling will also affect heat transfer and increase the extreme difference in cooling rate of the wire rod due to the large number of bubbles attached to the surface of the wire rod during heat exchange. The Si, Mn or Cr components in the wire rod are relatively high. Affected by the hardenability segregation, the overcooling position of the wire rod is more likely to form a martensitic structure that is unfavorable to the uniformity of the organization and drawing, which seriously affects the plasticity of the wire rod and causes wire breakage under large drawing amount. On the other hand, the cost of alloying elements such as Nb, V, and Ti is relatively high. As the amount used increases, the material cost will increase. Reducing or eliminating micro-alloy components for the purpose of reducing costs will bring about a large loss of strength and toughness. The required drawing amount in the subsequent drawing process increases, and the plasticity loss in the process is large, which will increase the risk of wire breakage during drawing.

[0005] 2. In order to obtain hot-rolled wire rods with better drawing performance, the existing process will reduce the cooling intensity of the Stelmore air-cooling line during phase transformation to extend the phase transformation time, and combine high-content hardenability components to increase the content of troostite in the organization that is beneficial to drawing and has good drawing hardening ability at a lower phase transformation temperature. However, on the one hand, due to the minimum cooling capacity of the Stelmore air-cooling line, the wire rod undergoes a short phase transformation incubation time, which will limit the increase in troostite content, and the soft phase ferrite content in the organization is relatively high, which limits the improvement in wire rod strength. Although in order to maximize the strength of the wire rod, some processes will choose to make bainite wire rods, for example: Patent CN109628837B discloses an ultra-fine bainite bridge cable steel, which uses C-Si-M The n-Cr-Nb composition design combines reheating after rolling to austenitize, cooling to low-temperature warm rolling and salt bath to obtain bainitic steel, but there are many processes and it takes a long time. At the same time, it is difficult to control the bainite phase transformation on the Stelmore air-cooling line of the steel plant, and the bainite distortion and dislocation density are relatively high. The resulting wire rod is relatively brittle and is easy to break during the steel plant's coiling process, downstream transportation and downstream unwinding process, affecting the batch production yield, easily generating raw material waste, and increasing the cost burden; on the other hand, the troostite wire rod produced by the Stelmore air-cooling line is limited by the continuous cooling phase transformation and the minimum cooling capacity. After controlled cooling, the residual stress and dislocation density are accumulated in the organization, which is high. After subsequent large deformation plastic deformation, it is easy to cause wire breakage or decreased torsional performance of the steel wire, which is difficult to meet application requirements. Summary of the invention

[0006] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a 2100MPa high-strength multiphase hot-rolled wire rod for bridge cables and a manufacturing method thereof, which can effectively control the abnormal network carbide and martensite structure, realize high-strength multiphase structure regulation and plastic matching, and is suitable for the large-drawing production of 2100MPa ultra-high-strength bridge cables, which is beneficial to reducing the risk of wire breakage.

[0007] The technical solution adopted by the present invention to solve its technical problem is:

[0008] A method for manufacturing a 2100MPa high-strength multiphase hot-rolled wire rod for bridge cables, the manufacturing method comprising:

[0009] The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.88%~0.92%, Si: 0.32%~0.52%, Mn: 0.65%~0.75%, Cr: 0.46%~0.56%, Mo: 0.2%~0.4%, P≤0.015%, S≤0.015%, and the rest is Fe and unavoidable impurities; the wire rod is spun at ≥930℃ After the wire rod is spun at high temperature, it is subjected to online molten salt end quenching isothermal treatment, so that the wire rod first passes through the front section of molten salt and is cooled at a cooling rate of ≥35℃ / s, enters the sorbite phase region from the austenite state, controls part of the austenite to transform into sorbite, and then passes through the rear section of molten salt to cool to the bainite phase for end quenching, controls the bainite phase transformation and isothermal tempering to relieve stress, and finally passes through roller slow cooling to obtain a hot-rolled wire rod with a microstructure including a complex phase structure composed of tempered sorbite and tempered bainite.

[0010] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes:

[0011] (1) Carbon: As an effective carbide strengthening element and austenite forming element, C is cheaper than other alloying elements. With the increase of carbon content, it can expand the austenite phase region, increase the volume fraction of cementite in the troostite structure, reduce the bainite start transformation temperature, and improve the tensile strength of the material. However, with the increase of carbon content, the tendency of central carbon segregation during the solidification of the steel billet will increase, which will increase the difficulty of controlling the decarburization and network carbides of the steel billet, make the cementite lamella thicker, increase the difficulty of isothermal stress relief during the subsequent molten salt treatment, and affect the toughness, plasticity and drawing properties of the material. Therefore, in order to take into account the high strength requirements of 2100MPa-grade bridge cables, reduce the difficulty of controlling network carbides, and adapt to the regulation of complex phase structure, the mass percentage of C is controlled to be 0.88%~0.92%.

[0012] (2) Silicon: The Si element is often used as a deoxidizer during the smelting process. It can inhibit the coarsening of cementite during the previous molten salt treatment so as to refine the interlamellar spacing of the troostite structure, which is beneficial to reduce the difficulty of stress relief in the subsequent molten salt isothermal tempering. After the wire rod is drawn into steel wire, it is beneficial to reduce the strength loss in the subsequent hot-dip galvanizing process. However, excessive silicon content will make the steel easier to decarburize when heated at high temperatures, prolong the transformation time during the phase transformation process, and is not conducive to controlling the formation of partial troostite structure after the wire rod undergoes a short phase transformation, which will reduce the toughness of the steel. Therefore, in order to adapt to the end quenching, the Si content is appropriately reduced, and the mass percentage of Si is controlled to be 0.32%~0.52%.

[0013] (3) Manganese: Mn can be added as a deoxidizer during the smelting process to ensure the smooth progress of the rolling process. At the same time, it can play a role in solid solution strengthening, increase the hardenability of the wire rod and the stability of austenite, which is beneficial to reducing the phase transformation temperature, and thus is beneficial to regulating the temperature of the sorbite phase region and controlling the network carbide by rapid cooling of molten salt. It can also promote the refinement of the interlamellar spacing of the sorbite structure, rapid nucleation, and improve the matrix strength. However, when the Mn content is too high, it will increase the steel's overheating sensitivity, grain coarsening and component segregation tendency, and increase the risk of martensite precipitation in the core of the wire rod. At the same time, it will delay the start time of the bainite phase transformation, reduce the diffusion activity of carbon, increase the difficulty of isothermal stress relief softening, and then lose the plasticity of the wire rod. Therefore, in order to take into account the high strength of the hot-rolled wire rod and reduce the difficulty of controlling the uniformity of the structure, the mass percentage of Mn is controlled to be 0.65%~0.75%.

[0014] (4) Chromium: Cr is a strong carbide-forming element that can improve the stability of austenite, prevent grain growth during hot rolling, play a role in solid solution strengthening and improving hardenability, and is beneficial to reducing the phase transition temperature and refining the spacing between cementite sheets. It is beneficial to improving the drawing performance and increasing the matrix strength. At the same time, it is beneficial to increase the work hardening rate of the wire rod during the wire drawing process and reduce the strength loss during the subsequent hot-dip galvanizing process of the steel wire. However, excessive Cr content will aggravate component segregation, increase the risk of low-temperature microstructure precipitation, reduce the activity of carbon in the steel, and significantly increase the difficulty of improving the plasticity of the wire rod. It is not conducive to isothermal stress relief during the subsequent molten salt treatment and will deteriorate the torsional performance of the steel wire. Therefore, the mass percentage of Cr is controlled to be 0.46%~0.56%.

[0015] (5) Molybdenum: The addition of Mo element can strongly inhibit the pearlite transformation during the isothermal treatment of molten salt end quenching. At the same time, Mo element can reduce the activity of C element, control the troostite content and lamellar thickness, which is beneficial to the regulation of complex phase structure. However, the cost of Mo element is relatively high, and excessive addition is not conducive to material cost control. Therefore, the mass percentage of Mo is controlled to 0.2%~0.4%.

[0016] (6) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.

[0017] The above-mentioned hot-rolled wire rod is different from the conventional high-carbon, high-silicon and micro-alloyed component system, and adopts the high-carbon, low-silicon and molybdenum component system of C-Si-Mn-Cr-Mo, without adding precious alloy elements such as Nb, V, and Ti, which can appropriately reduce the material cost, and at the same time regulate the hardenability of the wire rod, the peak precipitation temperature of sorbite and bainite, to provide favorable conditions for controlling the network carbides, the regulation of the complex phase structure and reducing the difficulty of high-temperature isothermal stress relief. On this basis, the appropriate spinning temperature is selected to promote the austenitization of the wire rod structure, to avoid the formation of network carbides in the spinning stage due to the low spinning temperature, to provide favorable conditions for increasing the temperature gradient and promoting the short-term phase transformation of the sorbite structure, and the wire rod is subjected to online molten salt end quenching isothermal treatment after spinning:

[0018] 1. Compared with the Stelmore air cooling line, which is difficult to control the network carbides due to the limited maximum cooling capacity, or combined with water mist or water bath cooling, the abnormal martensite structure is produced due to the uncontrollable cooling rate of the wire rod. On the one hand, when the wire rod passes through the front molten salt, the high heat exchange capacity of the molten salt can be used to promote the rapid cooling of the wire rod from the high-temperature austenite state, skipping the secondary cementite precipitation temperature range of 700~800℃, which can avoid the precipitation of network carbides along the grain boundary and deterioration of the wire rod structure uniformity, especially the plasticity and toughness of the wire rod, and improve the adverse effects of carbon segregation; on the other hand, the wire rod passes through the molten salt When the wire rod is quenched in the molten salt at the rear end, the residual austenite is controlled, and the formation of martensitic structure in the subsequent roller slow cooling process can be avoided, thereby improving the adverse effects of alloy element segregation, effectively improving the uniformity of the structure, and reducing the brittleness of the wire rod and the fluctuation of mechanical properties.

[0019] 2. Compared with the Stelmor air-cooled line, which is limited in cooling capacity due to continuous cooling or combined with water mist or water bath cooling, the rapid transformation of troostite is limited. On the one hand, the wire rod can be quickly cooled down and enter the troostite phase region after the front-stage molten salt treatment, forming a larger transition and driving force, and cooperate with Si and Mo to inhibit the transformation of pearlite, promote part of the high-temperature austenite to undergo a short-term phase transformation, and quickly transform to troostite with finer interlamellar spacing, providing favorable conditions for subsequent stress relief and controlled end quenching; on the other hand, due to uniform heat exchange, the temperature difference from the upper edge to the core of the same cross-section of the wire rod is smaller, which can promote uniform distribution of troostite and reduce fluctuations in mechanical properties.

[0020] 3. Compared with the Stelmore air cooling line, or combined with water mist or water bath cooling, the bainite phase transformation is difficult to control due to the uncontrollable cooling, or the bainite wire rod obtained by offline processing has high distortion and dislocation. The above manufacturing method adopts online molten salt end quenching isothermal. On the one hand, after the wire rod undergoes a short-term phase transformation in the troostite phase region through the front molten salt, the structure has part of the untransformed high-temperature austenite. After further entering the rear molten salt and cooling to the bainite phase region, the wire rod can keep the temperature consistent with the molten salt, promote the quenching of the untransformed high-temperature austenite in the wire rod into the bainite structure, make the bainite phase change more controllable, and use the end quenching to further improve the matrix strength, make up for the reduction of Si content and the non-addition of alloying elements such as Nb, V, and Ti. Strength loss. On the other hand, the temperature of the bainite phase region is relatively high. The bainite and bainite formed by the wire rod under high temperature isothermal for a longer time can be tempered to relieve stress, and the transformation will be strong and tough tempered bainite and tempered bainite structure, which can improve the strength and plasticity matching of the wire rod. After that, it is slowly cooled by rollers. Slow cooling can prevent the wire rod from cooling too fast during the cooling process, which leads to increased stress, and promote further toughening of the wire rod structure, improve the softening effect of the wire rod, and make the stress of the obtained complex phase structure lower and more evenly distributed, so as to avoid brittle fracture of the wire rod during downstream unwinding, transportation and even winding due to the brittleness of bainite. Compared with the offline processing process of re-austenitizing and heating, the process flow and production time of production are significantly shortened, and it has good industrial adaptability.

[0021] Selecting an appropriate heating furnace temperature before rolling can promote uniform diffusion of alloy components, reduce the impact of segregation, and avoid the risk of decarburization and burning caused by too long time in the furnace. In a preferred embodiment, before rolling, the heating furnace is controlled to have a soaking temperature of 1130-1180°C and a furnace time of 150-200 minutes.

[0022] Since the spinning temperature is relatively high, the restriction on the rolling temperature can be reduced, and appropriate rolling temperature and reduction control can be selected to avoid the high deformation resistance of the steel billet and the slow rolling speed caused by too low rolling temperature, and the risk of decarburization and grain growth caused by too high rolling temperature. The dynamic recrystallization and grain refinement of the final rolling process are promoted to further strengthen the matrix. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1100~1150℃, the final rolling temperature is 960~1100℃, and the final rolling reduction is 24%~30%.

[0023] The molten salt temperature of the front-stage molten salt is in the troostite phase region. The lower the molten salt temperature and the longer the treatment time, the greater the supercooling and driving force can be formed, driving the rapid nucleation of the troostite structure, refining the cementite lamellae, increasing the transformation of high-temperature austenite to troostite, increasing the content of tempered troostite in the complex phase structure, reducing the difficulty of high-temperature stress relief, and increasing the plasticity of the wire rod; however, if the molten salt temperature is too low and the treatment time is too long, the austenite structure will be transformed too much to troostite, which will limit the transformation of bainite and lose the strength of the wire rod; conversely, if the molten salt temperature is higher and the treatment time is shorter, the spacing between the troostite lamellae will become coarser, affecting the tempered troostite. content, increasing the proportion of untransformed high-temperature austenite and the difficulty of stress relief of the molten salt in the later stage, so that the tempered bainite in the complex phase structure increases and the strength of the wire rod is improved; but if the molten salt temperature is too high and the treatment time is too short, the sorbite phase transformation is too little and too coarse, the plasticity and drawing properties of the wire rod will be lost, and even the control of the network carbide will be affected. Therefore, the molten salt temperature and treatment time of the front-stage molten salt can be further controlled to promote the wire rod to quickly enter the sorbite phase region for short-term phase transformation, and make organizational preparations for the rear-stage molten salt treatment. In a preferred embodiment, the molten salt temperature of the front-stage molten salt is 510~530℃, and the treatment time is 10~30s.

[0024] Since the temperature difference of the wire rod from the high-temperature austenite state to the troostite phase temperature is large, selecting a larger molten salt circulation rate can control the molten salt temperature rise and improve the processing accuracy. In a preferred embodiment, the molten salt circulation rate of the front-stage molten salt is 260~380t / h, and the molten salt temperature rise is ≤10℃.

[0025] The molten salt temperature of the rear-stage molten salt is in the bainite phase region temperature. The lower the molten salt temperature is, the more it can promote the transformation of the untransformed austenite in the wire rod to the bainite structure for terminal quenching. However, if the molten salt temperature is too low, it is difficult to provide more thermal capacity for isothermal tempering, which will limit the tempering and stress relief effects and lose the plasticity of the wire rod. On the contrary, the higher the molten salt temperature is, the better the stress relief effect is, which can promote the toughening and softening of the wire rod structure. However, if the molten salt temperature is too high, it will limit the transformation of the austenite structure to bainite and lose the strength of the wire rod. The longer the treatment time is, the better the isothermal tempering stress relief effect is. However, if the treatment time is too long, the wire rod will be excessively lost. Strength or loss of strength and plasticity due to precipitation and coarsening of Cr; conversely, the shorter the treatment time, the lower the isothermal tempering effect and the plasticity of the wire rod. However, if the treatment time is too short, the stress and brittleness of the wire rod after quenching will be large, which will seriously lose the plasticity of the wire rod. Therefore, the molten salt temperature and treatment time of the rear-stage molten salt can be further controlled to control the bainite structure content. At the same time, after the wire rod is quenched at the end, isothermal tempering is performed to control the wire rod to enter the high-temperature isothermal range to relieve stress and improve the strength and plasticity matching of the wire rod. In a preferred embodiment, the molten salt temperature of the rear-stage molten salt is 420~470℃, and the treatment time is 90~180s.

[0026] Since the temperature difference between the front-end molten salt and the rear-end molten salt is relatively small, appropriately reducing the molten salt circulation volume can control the processing accuracy and reduce energy consumption. In a preferred embodiment, the molten salt circulation volume of the rear-end molten salt is 130~230t / h, and the molten salt temperature rise is ≤3°C.

[0027] In a preferred embodiment, the roller slow cooling controls the wire rod to slowly cool to below 300°C at a cooling rate of 0.35~0.55°C / s, which can prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. At the same time, it avoids the online time of the wire rod affected by too slow cooling rate, which can promote the rapid offline of the wire rod and improve production capacity.

[0028] A 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables, wherein the hot-rolled wire rod is manufactured by any of the above-mentioned methods for manufacturing the 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables.

[0029] The hot-rolled wire rod is designed with C-Si-Mn-Cr-Mo chemical composition, which is different from the existing high-carbon high-silicon microalloying composition system. The Si content in the system is relatively small. At the same time, the Mo element is added to limit the pearlite transformation, which can appropriately reduce the material cost. At the same time, it is different from the existing high-carbon pearlite steel or bainite steel. The microstructure type is a complex phase structure composed of tempered troostite and tempered bainite, in which the troostite has finer interlamellar spacing than pearlite, better strength and drawing hardening ability, and higher plasticity than bainite. The troostite is transformed into tempered troostite after tempering and stress relief. The plasticity of the matrix can be further improved. The bainite structure transformed by end quenching has higher distortion, dislocation density and strength than that of troostite. After tempering and stress relief, the bainite is transformed into tempered bainite, which can retain the strength characteristics of bainite, significantly improve the plasticity and toughness, weaken the brittleness of the structure, and obtain a strong and tough structure. Therefore, the bainite phase change, which is conventionally regarded as an abnormal structure, can be made controllable and its strength characteristics can be utilized to improve the strengthening effect of carbon elements, compensate for the strength loss caused by reducing Si content and not adding alloying elements such as Nb, V, Ti, and improve the overall strength and plasticity of the wire rod.

[0030] The finer the lamellar spacing of the tempered troostite is, the more beneficial it is to improving the strength and drawing hardening ability. In a preferred embodiment, the lamellar spacing of the tempered troostite is 70-120 mm.

[0031] The greater the proportion of tempered bainite in the multiphase structure, the higher the matrix strength and the lower the plasticity. In a preferred embodiment, the volume percentage of the tempered bainite is 55% to 60%.

[0032] In a preferred embodiment, the network carbide level of the hot-rolled wire rod is level 0, which can avoid the adverse effects of the network carbide on the uniformity of the wire rod structure and the drawing processing performance, and is more suitable for large-scale drawing processing and wire making.

[0033] The abnormal network carbide and martensite structures of the hot-rolled wire rod are effectively controlled, and the complex phase structure is evenly distributed, which is beneficial to reducing the fluctuation of the mechanical properties, drawing and torsion processing performance of the wire rod. In a preferred embodiment, the same circle difference of the mechanical properties of the hot-rolled wire rod is less than 60MPa.

[0034] In a preferred embodiment, the diameter of the hot-rolled wire rod is 8.0~15mm, the tensile strength is 1530~1560MPa, and the cross-sectional shrinkage rate is 30%~35%. The hot-rolled wire rod has a high tensile strength, which is beneficial to the manufacture of bridge cable steel wire through large drawing volume processing and quickly reaching the 2100MPa strength grade. It has a good cross-sectional shrinkage rate, which can significantly reduce the brittleness of the wire rod, and can effectively avoid breakage during the coiling and unwinding process of downstream users or during transportation or coiling of steel mills, thereby improving the stability of mass production. At the same time, it is beneficial to reduce the risk of wire breakage during large-volume drawing of wire rod processing, thereby improving the yield rate, which is beneficial to the stable production of bridge cables.

[0035] Compared with the prior art, the beneficial effects of the present invention are at least:

[0036] (1) In view of the current situation that after the existing high-carbon pearlite steel content and alloy content are increased, the deteriorated structures such as network carbides and martensite are difficult to control during the production process, and wire breakage is very likely to occur during subsequent large-volume drawing processing, the manufacturing method of the present invention combines the high-carbon, low-silicon, molybdenum-containing chemical composition design with the online molten salt end quenching isothermal technology, and can use the online ultra-fast cooling controlled cooling production line to control the wire rod to quickly enter the bainite phase region from the high-temperature austenite state, skipping the network carbide precipitation temperature range, and undergo a short-term phase transformation, and then control the wire rod to be in the bainite phase region. The temperature is lowered isothermally rather than continuously cooled, and the end quenching of the wire rod without transformation into high-temperature austenite is controlled to control the content of bainite structure. With isothermal tempering, the stress relief of the wire rod in the high-temperature isothermal range is controlled to improve the strength-plasticity matching of the wire rod. After that, the slow cooling on the roller promotes further toughening of the wire rod structure, which can effectively control the deterioration of structures such as network carbides and martensite. Compared with offline processing, it has fewer steps, shorter processes and higher efficiency, which can effectively improve the brittleness of the structure, reduce the fluctuation of mechanical properties, and avoid breakage during winding, transportation or downstream unwinding. It has good industrial adaptability.

[0037] (2) In view of the current situation that the existing high-carbon and high-silicon pearlite steel limits the manufacturing and cost of 2100MPa-level bridge cables, the hot-rolled wire rod of the present invention adopts C-Si-Mn-Cr-Mo chemical composition, and the microstructure type is a complex phase structure composed of tempered bainite and tempered bainite. The abnormal network carbide and martensite structures are effectively controlled, and the complex phase structure is evenly distributed. The bainite phase change that is conventionally regarded as an abnormal structure can be made controllable and its strength characteristics can be utilized to compensate for the strength loss caused by reducing the Si content and not adding alloying elements such as Nb, V, and Ti, thereby improving the overall strength and plasticity of the wire rod, achieving a tensile strength of 1530~1560MPa and a cross-sectional reduction rate of 30%~35%. It is used in the manufacture of 2100MPa-level ultra-high strength bridge cables and other application fields, which is beneficial to reducing the risk of wire breakage under large drawing processing, improving the yield rate of bridge cables, and facilitating cost control, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0039] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;

[0040] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;

[0041] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION

[0042] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:

[0043] A preferred embodiment of the manufacturing method of the 2100MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.91%, Si: 0.5%, Mn: 0.65%, Cr: 0.46%, Mo: 0.29%, P: 0.010%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt end quenching isothermal → roller slow cooling → coiling, specifically:

[0044] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, reduce segregation and control decarburization, and after the steel billet leaves the heating furnace, roll the steel billet into a wire with a diameter of 11mm through a rolling line, select appropriate rolling temperature and reduction, promote dynamic recrystallization and refine grains during the final rolling process, specifically: control the heating furnace soaking temperature to 1145°C, and the furnace time to 1 65min, the initial rolling temperature is 1120℃, the final rolling temperature is 975℃, and the final rolling reduction is 29%; the wire-spinning process is used to make the wire rods out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. The appropriate wire-spinning temperature is selected to make the wire rods in a high-temperature austenite state to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a larger temperature gradient later, which provides favorable conditions for promoting the rapid phase transformation of sorbite. Specifically, the wire-spinning temperature is controlled to be 945℃.

[0045] The online molten salt terminal quenching isothermal treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 37°C / s, and quickly skips the network carbide precipitation interval from the high-temperature austenite state to the sorbite phase region for a short-term phase transformation, inhibits the formation of network carbides, and promotes the phase transformation of part of the high-temperature austenite to the sorbite. After that, the wire rod is conveyed by a roller through the second salt bath tank for the rear molten salt treatment, and the untransformed part of the structure is controlled. The high-temperature austenite enters the bainite phase region for end quenching to control the bainite structure content. At the same time, the wire rod is isothermally tempered after end quenching to control the stress relief of the wire rod in the high-temperature isothermal range and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 510°C, the molten salt circulation volume is 330t / h, the molten salt temperature rise is ≤10°C, and the processing time is 30s; the molten salt temperature of the rear section is 420°C, the molten salt circulation volume is 230t / h, the molten salt temperature rise is ≤3°C, and the processing time is 90s.

[0046] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 298°C at a cooling rate of 0.35°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.

[0047] Comparative Example 1:

[0048] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor air cooling, specifically: the heating furnace soaking temperature is controlled to be 1080°C, the furnace time is 210min, the initial rolling temperature is 1040°C, the final rolling temperature is 890°C, and the spinning temperature is 855°C; the Stelmor strong air cooling adopts an air volume of 260,000 m per fan 3 / h, open 1~6# fans at 75%, cool the wire rod to 675℃ at a cooling rate of 7.5℃ / s, and then open 7~14# fans at 20%, cool the wire rod to 290℃ at a cooling rate of 2.4℃ / s, and obtain the hot-rolled wire rod product after it comes off the line.

[0049] Comparative Example 2:

[0050] A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1100°C, the furnace time is 180min, the initial rolling temperature is 1065°C, the final rolling temperature is 915°C, the spinning temperature is 895°C, and after the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 34°C / s, and the hot-rolled wire rod finished product is obtained after it is off the line. Embodiment 2:

[0051] A preferred embodiment of the manufacturing method of the 2100MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.89%, Si: 0.52%, Mn: 0.68%, Cr: 0.56%, Mo: 0.28%, P: 0.010%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt end quenching isothermal → roller slow cooling → coiling, specifically:

[0052] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, reduce segregation and control decarburization, and after the steel billet leaves the heating furnace, roll the steel billet into a wire with a diameter of 13mm through a rolling line, select appropriate rolling temperature and reduction, promote dynamic recrystallization and refine grains during the final rolling process, specifically: control the heating furnace soaking temperature to 1160°C, and the furnace time to 1 80min, the initial rolling temperature is 1135℃, the final rolling temperature is 990℃, and the final rolling reduction is 27%; the wire-spinning process is used to make the wire rods out of the rolling line through the wire-spinning mechanism into wire rods, and the wire rods are spread on the rollers and transported along the rollers. The appropriate wire-spinning temperature is selected to make the wire rods in a high-temperature austenite state to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a larger temperature gradient later, which provides favorable conditions for promoting the rapid phase transformation of sorbite. Specifically, the wire-spinning temperature is controlled to be 955℃.

[0053] The online molten salt terminal quenching isothermal treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 37°C / s, and quickly skips the network carbide precipitation interval from the high-temperature austenite state to the sorbite phase region for a short-term phase transformation, inhibits the formation of network carbides, and promotes the phase transformation of part of the high-temperature austenite to the sorbite. After that, the wire rod is conveyed by a roller through the second salt bath tank for the rear molten salt treatment, and the untransformed part of the structure is controlled. The high-temperature austenite enters the bainite phase region for end quenching to control the bainite structure content. At the same time, the wire rod is isothermally tempered after end quenching to control the stress relief of the wire rod in the high-temperature isothermal range and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 517°C, the molten salt circulation volume is 360t / h, the molten salt temperature rise is ≤10°C, and the processing time is 26s; the molten salt temperature of the rear section is 438°C, the molten salt circulation volume is 180t / h, the molten salt temperature rise is ≤3°C, and the processing time is 110s.

[0054] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 295°C at a cooling rate of 0.4°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.

[0055] Comparative Example 3:

[0056] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which differs from that of Example 2 in that: when the wire rod is treated with a front-stage molten salt, the temperature of the wire rod is cooled at a cooling rate of 39°C / s, the molten salt temperature of the front-stage molten salt is 500°C, and the treatment time is 40s; a hot-rolled wire rod finished product is obtained after it comes off the line.

[0057] Comparative Example 4:

[0058] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which differs from that of Example 2 in that: when the wire rod is treated with a front-end molten salt, the temperature of the wire rod is cooled at a cooling rate of 36°C / s, the molten salt temperature of the front-end molten salt is 545°C, and the treatment time is 10s; a hot-rolled wire rod finished product is obtained after the wire rod is off the line. Embodiment 3:

[0059] A preferred embodiment of the manufacturing method of the 2100MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.88%, Si: 0.43%, Mn: 0.75%, Cr: 0.53%, Mo: 0.40%, P: 0.015%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt end quenching isothermal → roller slow cooling → coiling, specifically:

[0060] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, reduce segregation and control decarburization, and after the steel billet leaves the heating furnace, roll the steel billet into a wire with a diameter of 15mm through a rolling line, select appropriate rolling temperature and reduction, promote dynamic recrystallization and refine grains during the final rolling process, specifically: control the heating furnace soaking temperature to 1180°C, and the furnace time to 1 The initial rolling temperature is 1150℃, the final rolling temperature is 1100℃, and the final rolling reduction is 24%. The spinning process is used to make the wire rods out of the rolling line into wire rods through the spinning mechanism. The wire rods are spread on the rollers and transported along the rollers. The appropriate spinning temperature is selected to make the wire rods in a high-temperature austenite state to avoid the formation of network carbides in the spinning stage caused by too low spinning temperature, so as to form a larger temperature gradient later, which provides favorable conditions for promoting the rapid phase transformation of sorbite. Specifically, the spinning temperature is controlled to be 965℃.

[0061] The online molten salt terminal quenching isothermal treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 38°C / s, and quickly skips the network carbide precipitation interval from the high-temperature austenite state to the sorbite phase region for a short-term phase transformation, inhibits the formation of network carbides, and promotes the phase transformation of part of the high-temperature austenite to the sorbite. After that, the wire rod is conveyed by a roller through the second stage salt bath tank for the rear stage molten salt treatment, and the untransformed part of the structure is controlled. The high-temperature austenite enters the bainite phase region for end quenching to control the bainite structure content. At the same time, the wire rod is isothermally tempered after end quenching to control the stress relief of the wire rod in the high-temperature isothermal range and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 523°C, the molten salt circulation volume is 380t / h, the molten salt temperature rise is ≤10°C, and the processing time is 17s; the molten salt temperature of the rear section is 456°C, the molten salt circulation volume is 150t / h, the molten salt temperature rise is ≤3°C, and the processing time is 155s.

[0062] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 290°C at a cooling rate of 0.45°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.

[0063] Comparative Example 5:

[0064] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that: the molten salt temperature of the rear-stage molten salt is 400° C., and the processing time is 80 seconds; and a hot-rolled wire rod finished product is obtained after the production line is off the line.

[0065] Comparative Example 6:

[0066] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that: the molten salt temperature of the rear-stage molten salt is 490° C., and the processing time is 210 s; and a finished hot-rolled wire rod is obtained after the product is off the line. Embodiment 4:

[0067] A preferred embodiment of the manufacturing method of the 2100MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.92%, Si: 0.32%, Mn: 0.71%, Cr: 0.47%, Mo: 0.20%, P: 0.013%, S: 0.013%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt end quenching isothermal → roller slow cooling → coiling, specifically:

[0068] The rolling process is used to heat a steel billet with a specification of 180mm×180mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, reduce segregation and control decarburization, and after the steel billet leaves the heating furnace, roll the steel billet into a wire with a diameter of 8mm through a rolling line, select appropriate rolling temperature and reduction, promote dynamic recrystallization and refine grains during the final rolling process, specifically: control the heating furnace soaking temperature to 1180°C, the furnace time to 15 0min, the initial rolling temperature is 1150℃, the final rolling temperature is 1100℃, and the final rolling reduction is 30%; the wire-spinning process is used to make the wire rods out of the rolling line through the wire-spinning mechanism into wire rods, and the wire rods are spread on the rollers and transported along the rollers. The appropriate wire-spinning temperature is selected to make the wire rods in a high-temperature austenite state to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a larger temperature gradient later, which provides favorable conditions for promoting the rapid phase transformation of sorbite. Specifically, the wire-spinning temperature is controlled to be 930℃.

[0069] The online molten salt terminal quenching isothermal treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 35°C / s, and quickly skips the network carbide precipitation interval from the high-temperature austenite state to the sorbite phase region for a short-term phase transformation, inhibits the formation of network carbides, and promotes the phase transformation of part of the high-temperature austenite to the sorbite. After that, the wire rod is conveyed by a roller through the second stage salt bath tank for the rear stage molten salt treatment, and the untransformed part of the structure is controlled. The high-temperature austenite enters the bainite phase region for end quenching to control the bainite structure content. At the same time, the wire rod is isothermally tempered after end quenching to control the stress relief of the wire rod in the high-temperature isothermal range and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 530°C, the molten salt circulation volume is 260t / h, the molten salt temperature rise is ≤10°C, and the processing time is 10s; the molten salt temperature of the rear section is 470°C, the molten salt circulation volume is 130t / h, the molten salt temperature rise is ≤3°C, and the processing time is 180s.

[0070] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, which leads to increased stress, and promotes further toughening of the wire rod structure and improves the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 285°C at a cooling rate of 0.55°C / s; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.

[0071] Comparative Example 7:

[0072] A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the method is manufactured according to a process flow of rolling → spinning → online molten salt end quenching isothermal → air cooling, and the air cooling process is performed by opening a heat preservation cover, and conveying the wire rod through a second salt bath tank by a conveyor roller, and controlling the wire rod to be slowly cooled to 280°C at a cooling rate of 1.5°C / s. After the hot-rolled wire rod is off the line, a finished product is obtained, and the tensile strength is 1567MPa and the cross-sectional shrinkage rate is 28%.

[0073] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 1 to 6 were subjected to microstructure and performance tests, and the obtained comparative results are shown in Table 1 below:

[0074] Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods

[0075]

[0076] The interlamellar spacing in Table 1 above is the interlamellar spacing of tempered troostite or troostite. From the comparison results of Example 1 and Comparative Example 1, it can be seen that the carbon content and alloy content of high-carbon pearlite steel are constantly increasing. Under the conventional controlled rolling and cooling production line, the deteriorated structures such as net carbon and martensite are increasingly difficult to control during the production process. The uncontrollable cooling rate weakens the strengthening effect, resulting in insufficient strength and plasticity and large fluctuations in mechanical properties. The present invention combines the online molten salt end quenching isothermal technology with the online molten salt ultra-fast cooling rate technology through the C-Si-Mn-Cr-Mo chemical composition design. The risk of abnormal tissues such as reticular carbon and martensite produced by the C element is effectively avoided, and the pearlite transformation is inhibited by Mo, thereby improving the strengthening effect of the carbon element. The microstructure type is a complex phase structure composed of tempered troostite and tempered bainite. It can be seen from the results of Examples 1 to 4 that the overall strength and plasticity of the wire rod are improved, and the product tensile strength can reach 1530~1560MPa, and the cross-sectional shrinkage rate is 30%~35%. It is used in the manufacture of 2100MPa ultra-high strength bridge cables and other application fields, which is beneficial to reduce the risk of wire breakage in subsequent large-volume drawing processing.

[0077] From the comparison results of Example 1 and Comparative Example 2, it can be seen that selecting an appropriate spinning temperature promotes austenitization of the wire rod structure and avoids the formation of network carbides during the spinning stage due to too low spinning temperature, which provides favorable conditions for increasing the temperature gradient and promoting the short-term phase transformation of the troostite structure.

[0078] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature of the front-stage molten salt and the longer the treatment time, the greater the supercooling and driving force can be formed, the tempered troostite content in the multiphase structure can be increased, the difficulty of high-temperature stress relief can be reduced, and the plasticity of the wire rod can be increased. However, if the molten salt temperature is too low and the treatment time is too long, the bainite transformation will be limited and the strength of the wire rod will be lost.

[0079] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature of the front stage molten salt and the shorter the treatment time, the coarser the spacing between the troostite lamellae becomes, which increases the tempered bainite in the complex phase structure. However, if the molten salt temperature is too high and the treatment time is too short, the troostite phase transformation is too little and too coarse, which will cause loss of wire rod plasticity and drawing performance.

[0080] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the lower the molten salt temperature of the rear-stage molten salt is, the more it can promote the transformation of the untransformed austenite in the wire rod to the bainite structure for terminal quenching, and the shorter the treatment time is, the lower the isothermal tempering effect is. However, if the salt temperature is too low and the treatment time is too short, it is difficult to provide more thermal capacity for isothermal tempering. After the wire rod is quenched, the structural stress and brittleness are large, which will seriously lose the plasticity of the wire rod.

[0081] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the higher the molten salt temperature of the latter molten salt and the longer the treatment time, the better the stress relief effect. However, if the molten salt temperature is too high and the treatment time is shorter, the transformation of austenite structure to bainite will be limited, resulting in excessive loss of wire rod strength or loss of strength and plasticity due to precipitation and coarsening of Cr.

[0082] From the comparison results of Example 4 and Comparative Example 7, it can be seen that slow roller cooling can prevent the wire rod from cooling too fast during the cooling process, which will cause an increase in stress, promote further toughening of the wire rod structure, and improve the softening effect of the wire rod.

[0083] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for manufacturing a 2100MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.88%~0.92%, Si: 0.32%~0.52%, Mn: 0.65%~0.75%, Cr: 0.46%~0.56%, Mo: 0.2%~0.4%, P≤0.015%, S≤0.015%, and the rest is Fe and unavoidable impurities; the wire rod is spun at ≥930℃ After the wire rod is spun at high temperature, it is subjected to online molten salt end quenching isothermal treatment, so that the wire rod first passes through the front section of molten salt and is cooled at a cooling rate of ≥35℃ / s, enters the sorbite phase region from the austenite state, controls part of the austenite to transform into sorbite, and then passes through the rear section of molten salt to cool to the bainite phase for end quenching, controls the bainite phase transformation and isothermal tempering to relieve stress, and finally passes through roller slow cooling to obtain a hot-rolled wire rod with a microstructure including a complex phase structure composed of tempered sorbite and tempered bainite.

2. The method for manufacturing 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the soaking temperature of the heating furnace is controlled to be 1130-1180° C., and the time in the furnace is 150-200 minutes.

3. The method for manufacturing 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1100-1150° C., the final rolling temperature is controlled to be 960-1100° C., and the final rolling reduction is controlled to be 24%-30%.

4. The method for manufacturing 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: The molten salt temperature of the front-stage molten salt is 510-530° C., and the processing time is 10-30 seconds; the molten salt temperature of the rear-stage molten salt is 420-470° C., and the processing time is 90-180 seconds.

5. The method for manufacturing 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 4, characterized in that: The molten salt circulation volume of the front-stage molten salt is 260-380 t / h, and the molten salt temperature rise is ≤10°C; the molten salt circulation volume of the rear-stage molten salt is 130-230 t / h, and the molten salt temperature rise is ≤3°C.

6. The method for manufacturing 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 4, characterized in that: The roller slow cooling controls the wire rod to be slowly cooled to below 300° C. at a cooling rate of 0.35-0.55° C. / s.

7. A 2100MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing 2100MPa-grade high-strength multi-phase hot-rolled wire rod for bridge cables as described in any one of claims 1 to 6.

8. The 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The interlamellar spacing of the tempered bainite is 70-120 mm, and the volume percentage of the tempered bainite is 55%-60%.

9. The 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is less than 60 MPa.

10. The 2100MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The hot-rolled wire rod has a diameter of 8.0-15 mm, a tensile strength of 1530-1560 MPa, and a cross-sectional shrinkage of 30%-35%.

Citation Information

Patent Citations

  • An ultrafine bainitic bridge cable steel and its preparation method

    CN109628837B

  • Ferrite and pearlite structure SWRH72BCr-1 prestressed hot-rolled wire rod and preparation method thereof

    CN117448680A

  • 2000MPa-grade vanadium-containing 55SiCr spring steel hot-rolled wire rod and production process thereof

    CN117888034A